2022
DOI: 10.3390/ijerph191710957
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Support Practices for Infants Born <750 Grams or <25 Weeks Gestation: A Call for More Research

Abstract: With advances in medical care and efforts to care for continually smaller and younger preterm infants, the gestational age of viability has decreased, including as young as 21 or 22 weeks of gestation [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Conversely, a single-center cohort study (using historical controls) of infants < 750 g at birth found a reduced incidence of NEC and death after implementing slow advancement protocol (but higher rates of cholestasis) [42]. This result may due to the implementation of a SFP that didn't previously exist or indicate that micropremies (< 750 g or < 25 weeks' gestation) are a unique population [43]. Preterm growth restricted infants and infants with a history of absent or reverse end diastolic flow may also be at increased risk for NEC and TPNassociated liver injury [44][45][46][47].…”
Section: Feeding Advancementmentioning
confidence: 97%
“…Conversely, a single-center cohort study (using historical controls) of infants < 750 g at birth found a reduced incidence of NEC and death after implementing slow advancement protocol (but higher rates of cholestasis) [42]. This result may due to the implementation of a SFP that didn't previously exist or indicate that micropremies (< 750 g or < 25 weeks' gestation) are a unique population [43]. Preterm growth restricted infants and infants with a history of absent or reverse end diastolic flow may also be at increased risk for NEC and TPNassociated liver injury [44][45][46][47].…”
Section: Feeding Advancementmentioning
confidence: 97%